Infrared thermometry for drought phenotyping of inter and intra specific upland rice lines - Guimarães, C.M.; Stone, LF; Lorieux, Mathias; Oliveira, J.P. de; Alencar, G; Dias, R.A.A. (FapUNIFESP, 2010)
The purpose of the present study was to evaluate the use of infrared thermometry in the characterization of inter specific (Oryza glaberrima x Oryza sativa cv Caiapó) and intra specific upland rice lines for drought tolerance. The experiment, carried out at Porangatu in the State of Goiás, was submitted to adequate soil moisture for up to 30 days following emergence when a moderate water stress treatment was imposed (about 50% of the applied irrigation in a control plot in which adequate conditions of soil moisture were maintained). It has been observed that lines with higher grain yields under water stress produced taller plants with denser panicles and well-formed grains as well as lower spikelet sterility. A positive correlation between canopy temperature and spikelet sterility was observed; and a negative correlation existed between canopy temperature and 100-grain weight, plant height, tiller fertility, and grain yield. Except for tiller fertility, all components showed correlation with grain yield; in the case of spikelet sterility, the relationship was negative. It has been inferred that O. glaberrima confers to its lines higher rusticity where water stress is concerned, and that infrared thermometry is an important supporting tool for phenotyping drought tolerance.